2015
DOI: 10.1111/cge.12627
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of health monitoring and disease self‐management in Australian adults with neurofibromatosis type 1: strategies to improve care

Abstract: Lifelong health monitoring is recommended in neurofibromatosis type 1 (NF1) because of the progressive and unpredictable range of disabling and potentially life-threatening symptoms that arise. In Australia, strategies for NF1 health surveillance are less well developed for adults than they are for children, resulting in inequalities between pediatric and adult care. The aims of this study were to determine the uptake of health monitoring and capacity of adults with NF1 to self-manage their health. Australian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…When we focus on patient characteristics, the need for communication support depends on selfmanagement and communication skills [27,[31], [32], [33]]. The level of these skills is affected by age [34], patient activation level [35], educational level and socio economic status (SES) [36], sex [37], illness burden [38] and health literacy [ [39], [40], [41]]. In our systematic review we did not find a relation between communication outcomes and these factors though [13], which is confirmed in the current study.…”
Section: Discussion and Conclusion 41 Discussionmentioning
confidence: 99%
“…When we focus on patient characteristics, the need for communication support depends on selfmanagement and communication skills [27,[31], [32], [33]]. The level of these skills is affected by age [34], patient activation level [35], educational level and socio economic status (SES) [36], sex [37], illness burden [38] and health literacy [ [39], [40], [41]]. In our systematic review we did not find a relation between communication outcomes and these factors though [13], which is confirmed in the current study.…”
Section: Discussion and Conclusion 41 Discussionmentioning
confidence: 99%
“…Adultos com manifestações complexas devem comparecer a um local especializado ou clínica de NF1, enquanto aqueles com sintomas leves devem estar cientes de quando procurar aconselhamento médico. Sintomas como dor crônica, aumento rápido de um tumor existente e / ou déficit neurológico garantem pronto atendimento médico (CRAWFORD et al, 2015).…”
Section: Discussionunclassified
“…Further research into why adults may be unable to attend specialty rare disease clinics (for example, because nearby clinics do not accept adult patients) or choose not to attend these clinics (for example, because of personal preference or financial constraints) would be valuable in guiding a strategy for improving access to care. Research in Australia showed that many adults with NF1 did not receive regular specialist care due to a combination of these factors, including not knowing where to get care and not realizing the importance of continued monitoring in adulthood [ 18 ]. This indicates that educational awareness campaigns around the benefits of regular specialist care may increase the proportion of adults with NF1 attending specialty clinics.…”
Section: Discussionmentioning
confidence: 99%